Cases on optimizing the asset management process - Gonzalez-Prida, Vicente, 1975-; Parra, Carlos, 1970-; Crespo Márquez, Adolfo (Advances in logistics, operations, and management science (ALOMS) book series., 2022)
"This book explains and summarizes the processes (course of actions and the number of stages or steps to follow) and the reference frame (the essential support structure and the basic system) necessary for the implementation of the introduced maintenance management model (MMM) and will help managers, technology developers, scientists and engineers to adopt and implement optimum decision making based on techniques of maintenance and reliability in organizations"--